Innovation Management Model in Supporting Healthy Food Availability Through The Development of Zoning-Based Organic Farming - Subejo Subejo; Irham Irham; Rikardo Simarmata; Arif Wahyu Widada; Azizatun Nurhayati; Esti Anantasari; Laksmi Yustika Devi (STI Policy and Management Journal, 2022)
The importance of providing healthy food has become a great concern in agricultural development. The innovation of zoning-based organic farming development is the prospective solution not only to increase the production capability of healthy food but also to improve the quality of land and the environment, as well as to increase business efficiency, and to improve agricultural product price. The development of zoning-based organic farming is also in line with the national policy in agriculture, namely the corporate-based agricultural zoning approach. Apart from that, the development of organic agriculture must be an upstream-downstream approach so that integrative management system is strongly needed, starting from on-farm processing to marketing of the organic products. The implementation of zoning-based organic farming management will involve many related stakeholders, especially farmers, farmer groups, cooperatives, related local governmental agencies and business partners. This approach certainly requires a clear legal basic support related to the organic agriculture zoning so that the sustainability of organic farming can be appropriately maintained. Therefore, the idea of making District Head Regulation (called Peraturan Bupati) as the legal protection for the management system for organic farming zoning is the right choice. Thus, if the design of this governance model can run well, then the hope that the zoning-based organic farming approach will improve the welfare of farmers may come true